2015
DOI: 10.3923/ajbs.2015.72.82
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nano Iron Chelate Fertilizer on Iron Absorption and Saffron (Crocus sativus L.) Quantitative and Qualitative Characteristics

Abstract: In order to investigate the effect of nano iron chelate and compare to EDDHSA chelate on saffron, a factorial experiment with six treatments and three replications was conducted in saffron research farm of Shahed University in crop year of 2013-2014. Treatments included iron fertilizer at two levels of application of nano iron chelate fertilizer and iron chelate fertilizer with base of EDDHSA and the second agent was amount of fertilizer at three levels of 0,5 and 10 kg haG 1 . Number of flowers, flowers perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Iron nano fertilizers have stimulatory effects on plant growth. The stimulating effect of the Fe nano chelate fertilizer applications the growth of peanut shoots and roots (Rui et al, 2016), mung bean (Karimi et al, 2014), saffron (Maleki Farahani et al, 2015) and poinsettia (Kaviani et al, 2016) has been reported. The increased Fe and carbohydrate availability in the Fe treated plants might be the reason for their increased shoot and root growth.…”
Section: Disscusionmentioning
confidence: 99%
“…Iron nano fertilizers have stimulatory effects on plant growth. The stimulating effect of the Fe nano chelate fertilizer applications the growth of peanut shoots and roots (Rui et al, 2016), mung bean (Karimi et al, 2014), saffron (Maleki Farahani et al, 2015) and poinsettia (Kaviani et al, 2016) has been reported. The increased Fe and carbohydrate availability in the Fe treated plants might be the reason for their increased shoot and root growth.…”
Section: Disscusionmentioning
confidence: 99%
“…Farahani et al (2015) [ 49 ] studied the effect of iron-chelated nanofertilizers on the quantitative and qualitative characteristics of saffron. They found that this fertilizer is more effective than conventional iron-chelated fertilizers.…”
Section: Resultsmentioning
confidence: 99%
“…The best LAI of 5.1 was recorded in wheat cultivar Raijav after foliar treatment of iron (2%) during the tillering stage [17]. A correlation of the impact of nano iron chelate compost and standard chelate EDDHSA on the quantitative and subjective qualities of saffron (Crocus sativus L.) uncovered that nano-based iron manure was more successful than standard manure and that use of nano manure at 5 kg/ha was better in expanding the LAI than the most significant level of 3.45 [40].…”
Section: Leaf Area Index (Lai)mentioning
confidence: 99%